High Levels of SIRT1 Expression as a Protective Mechanism Against Disease-Related Conditions - Elibol, Birsen; Kilic, Ulkan (Frontiers in Endocrinology, 2018)
SIRT1 protein, a member of Silent Information Regulator 2 (Sir2) protein family, have gained considerable attention as epigenetic regulators for a great area in the human physiology. Changes in sirtuin expression are critical in several diseases, including metabolic syndrome, cardiovascular diseases, cancer and neurodegeneration. Here, we provide an overview of the association of the increasing level of SIRT1 protein for regulating some disease related conditions such as obesity, cardiovascular diseases and neurodegeneration. This review also provides a detailed molecular understanding of the interaction of the some basic molecules with increasing SIRT1 levels rather than reduction of the SIRT1 expression. In this context, the current approaches to enhancing the expression of SIRT1 points the importance of epigenetics in several age-related diseases to provide a healthy aging by developing novel therapies which can prevent or damp the progression of some diseases.